The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1103/physrevd.70.043503
|View full text |Cite
|
Sign up to set email alerts
|

Indirect search for dark matter: Prospects for GLAST

Abstract: Possible indirect detection of neutralino, through its γ-ray annihilation product, by the forthcoming GLAST satellite from our galactic halo, M31, M87 and the dwarf galaxies Draco and Sagittarius is studied. γ-ray fluxes are evaluated for two representative energy thresholds, 0.1 GeV and 1.0 GeV, at which the spatial resolution of GLAST varies considerably. Apart from dwarfs, which are described either by a modified Plummer profile or by a tidally-truncated King profile, fluxes are compared for halos with cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 72 publications
3
20
0
Order By: Relevance
“…where σv is the velocity-averaged cross section and N γ is the yield, called Q γ in Peirani et al (2004) and FPS. We have moved the constant factor 1/4π to be part of Φ cosmo because it is most easily understood as part of the attenuation of the gamma-ray flux over distance.…”
Section: Gamma-ray Fluxmentioning
confidence: 99%
“…where σv is the velocity-averaged cross section and N γ is the yield, called Q γ in Peirani et al (2004) and FPS. We have moved the constant factor 1/4π to be part of Φ cosmo because it is most easily understood as part of the attenuation of the gamma-ray flux over distance.…”
Section: Gamma-ray Fluxmentioning
confidence: 99%
“…Many authors have studied the feasibility of such a detection, using a large variety of cuspy and cored universal density profiles, reflecting the theoretical as well as the experimental uncertainties. Different works (Baltz et al 2000;Tyler 2002;Peirani et al 2004;Pieri & Branchini 2004;Bergström et al 2006) found that only the presence of a spike and/or an enhancement due to clumpiness and/or a more favourable combination of the unknown particle physics parameters could make the Draco dwarf galaxy observable with the Fermi-LAT. Strigari et al (2007) are optimistic about the detection of Draco with the Fermi-LAT in 5 years.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…That dSphs make good candidates for DM annihilation detection has been much discussed before, especially for the "classical", or pre-SDSS, dSphs [62,110,142,143,144,145]. The annihilation signal coming from Draco has been the subject of much research in recent years because of its relative proximity to the Earth [65,110,144,146,147,148,149,150].…”
Section: Predicted Annihilation Signals For Dwarf Spheroidalsmentioning
confidence: 99%